Laws relating to area management in the Bandon Bay area - Auidumrongtham, Pornvilai; Ruttanawut, Jiddarom; Khwanchaisakun, Phet (Journal of Humanities and Social Sciences Loei Rajabhat University, 2024)
The purpose of this research is to study laws and government agencies. with duties and powers to enforce laws for the management and administration of Bandon Bay Area and to recommend law enforcement for the management of Ban Don Bay area to be unified and effective By documentary research from books, textbooks, legal articles and electronic media related to the management of Ban Lon Bay area. Including collecting data in the area from government officials and stakeholders in the form of interviews based on research questions. and analyze the data according to the objectives set The results showed that Related laws include both international law and domestic law, which can be divided into 3 categories: law applicable to coastal seas; Laws applicable to the territorial sea and laws applicable to the exclusive economic zone seas Said for the management of Ban Don Bay area, the law and the three levels of government officials are the law for managing mangrove and coastal areas. Laws relating to the management of marine areas and laws on fisheries and aquaculture. The law empowers government agencies to enforce laws separately. causing a state of lack of unity in law enforcement Law enforcement in Bandon Bay area must therefore be integrated into the government sector. civil society and stakeholders By using legal mechanisms as a tool for management to achieve maximum efficiency. The researcher saw that Management of mangrove and coastal areas is the authority of the Department of Marine and Coastal Resources under the Marine and Coastal Resources Management Promotion Act B.E. 2558. Management of offshore areas is the authority of the Marine Department according to the Maritime in Thai waters 1903 and the Thai Vessels Act 1938. Fishery area management and aquaculture are the duties of the Department of Fisheries according to the Royal Ordinance on Fisheries 2015. It is therefore suggested that Land management and request for permission both directly and directly related to fisheries or aquaculture are the powers and duties of the Department of Fisheries. The management of other areas shall be the duties and powers of state agencies as specifically provided by law